ÜRİNOMUN PERKÜTAN NEFROSTOMİ VE DOUBLE J KATETER DRENAJI İLE TEDAVİSİ: BİR OLGU SUNUMU - ALAN, Cabir; TUNÇ, Burçin; DEMİRKESEN, Oktay (Cerrahpaşa Medical Journal, 2014)
Background.- Renal injuries can rarely be seen following non-penetrating traumas. Kidneys are the most commonly injured organs of urinary tract. Since genito-urinary traumas do not have specific symptoms, it is hard to diagnose. We presented a case of urinoma following non-penetrating renal trauma who is managed by percutaneus nephrostomy tube and indwelling ureteral catheter.